Trichomonas vaginalis and the human immunodeficiency virus (HIV): an integrative literature review: Trichomonas vaginalis and the human immunodeficiency virus (HIV): an integrative literature review (Health and Biosciences, 2025)
Trichomonas vaginalis is the parasite that causes trichomoniasis, a non-viral sexually transmitted infection that is widely prevalent worldwide and mostly affects women. The disease is transmitted mainly through unprotected sexual contact and is asymptomatic in most cases. Given the studies that point to T. vaginalis infection and a greater susceptibility to other sexually transmitted diseases, the aim of this study was to relate this disease to a greater susceptibility to HIV and to present scientific data that can be used to formulate prevention methodologies for both infections. An integrative literature review was carried out, covering the period from 2005 to 2021, based on articles indexed in the SciELO, Pubmed and LILACS databases. The descriptors chosen, according to the classification of health sciences descriptors (DeCS) were: “Trichomonas vaginalis”, ‘HIV’ and “Human Immunodeficiency”, combined in English, Portuguese and Spanish. The searches were conducted based on a guiding question and the articles were selected using pre-defined inclusion and exclusion criteria. Based on the results, it was observed that the main variables related to both infections were: female gender; white and black race/color; being pregnant; single, divorced and widowed marital status; low schooling and income and behavioral variables (multiple sexual partners and alcohol abuse). In relation to the guiding question of the review, it was possible to conclude that the presence of T. vaginalis infection increases the risk of the individual becoming infected with HIV and vice-versa, and that interventions and methodologies aimed at knowledge and prevention of both diseases are necessary.
Keywords: human immunodeficiency; sexually transmitted infections; trichomoniasis; HIV.